Analysis of motor activities of professional soccer players during the 2014 World Cup in Brazil - Chmura, P.; Andrzejewski, M.; Konefal, M.; Mroczek, D.; Rokita, A.; Chmura, J. (Journal of Human Kinetics, 2017)
The aim of the present study was to analyze motor activities of soccer players in seven consecutive rounds of matches of the 2014 World Cup in Brazil and to compare the performance of the world champions, the German national team with other participating teams. The study sample comprised 905 observations of 340 soccer players, who played full-time matches in all seven rounds of the tournament. The study was conducted using data collected from the Castrol Performance Index, a kinematic game analysis system that records movements of players with semi-automatic cameras. The following variables were analyzed: total distance covered, the percentage of total distance covered at high intensity, the number of sprints, frequency of sprints and peak running speed. A statistically significant increase (p = 0.01) was noted in total distance covered, the percentage of distance covered at high intensity and total number of sprints, between the quarter-finals and semi-finals of the World Cup tournament in Brazil. The German national team covered a significantly longer total distance (p = 0.05) and had a greater percentage of distance covered at high intensity (p = 0.001) than players from other teams. The obtained results point to the necessity of development of players` aerobic endurance and speed-endurance abilities while preparing for top-level soccer tournaments. Winning a soccer championship requires players to run longer mean total distances and longer distances at high intensity during a single match.